Hubungan Antara Tingkat Konsumsi Zat Gizi Mikro, Status Imunisasi, dan Stunting Pada Balita Usia 12-24 Bulan di Desa Sangkan Gunung Sidemen Kabupaten Karangasem - Emi, Ni Putu; Mataram, I Komang Agusjaya; Nursanyoto, Hertog (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Stunting is a major nutritional problem of concern in Indonesia. Stunting is defined as a condition in which the nutritional status of a child is based on the height-for-age index (TB/U) with z-score -2SD. The purpose of this research is to find out relationship between levels of consumption of micronutrients, immunization status and stunting in toddlers aged 12-24 months in Sangkan Gunung Village Sidemen Karangasem Regency. This type of observational research with cross-sectional research design. The research sample consisted of 44 toddlers (12-24 months of age). The type of data used includes primary data, namely stunting status, consumption level of micronutrients (zinc, calcium, phosphorus), immunization status, as well as secondary data, namely the number of children under five and an overview of Sangkan Gunung Village. Sampling using simple random sampling technique. The results of the study found that 18.2% of children under five had stunting nutritional status, with 15.9% having a low consumption of zinc, 18.2% having a low consumption of calcium, 15.9% having a low consumption of phosphorus, and 2.3% having incomplete immunization status. Tthe Pearson Correlation statistical test showed that there was a significant relationship between the consumption level of micronutrients (zinc, calcium, phosphorus) and the stunting status in children under five (p = 0.015, 0.003, 0.004), and there is a non-significant relationship between immunization status and stunting status in toddlers (p = 0,313).Keywords: Stunting, Zinc, Calcium, Phosphorus, Immunization Status